The Application and Research of Digital Art in Architectural Decoration Design - Zhao, Donghua; Liu, Litong (Transactions on Social Science, Education and Humanities Research, 2024)
This paper aims to explore the application and research of digital art in the field of architectural decoration. With the continuous development and popularization of digital technology, digital art, as a new form of art expression, is gradually infiltrating into every aspect of architectural decoration. The introduction of digital art provides architectural designers and decorators with a broader space for creation and a richer way of expression, and also endows architectural works with more colorful artistic connotation and the atmosphere of The Times. Based on the concept and characteristics of digital art, this paper discusses the application practice of digital art in traditional and modern architectural decoration, analyzes its influence on architectural decoration style, spatial atmosphere and user experience, and prospects the future development trend of digital art in the field of architectural decoration.